Development of the genomic inflammatory index (GII) to assess key maternal antecedents associated with placental inflammation. (August 2021) - Oldenburg, Kirsi S.; Eaves, Lauren A.; Smeester, Lisa; Santos, Hudson P.; O'Shea, T. Michael; Fry, Rebecca C.
Abstract: Introduction: Placental inflammation is associated with a variety of adverse health outcomes, including poor pregnancy outcomes as well as later in life health. The current clinical methodologies for evaluating placental histology for inflammation are limited in their sensitivity. The objective of this study was to develop a genomic inflammatory index (GII) that can be utilized as a biomarker to effectively quantify and evaluate placental inflammation. Methods: RNA-sequencing of n = 386 placentas from the Extremely Low Gestational Age Newborn (ELGAN) cohort was conducted. Transcriptional data for a biologically-targeted set of 14 genes, selected for their established role in pro-inflammatory signaling pathways, were aggregated to construct the GII. Multiple linear regression models were used to examine relationships between 47 perinatal factors and the GII. Results: The GII demonstrated a nine-fold difference across subjects and displayed positive trends with other indicators of placental inflammation. Significant differences in the GII were observed for race where women who self-identified as Black displayed higher levels of placental inflammation than those who self-identified as White women (p < 0.001). Additionally, married Black women showed reduced placental inflammation compared to those who were unmarried (beta value: 0.828, p-value: 0.032). Placentas from women who were treated with steroids during the delivery of the infant displayed higher GII levels than those who were not (p = 0.023). Discussion: Overall, the GII demonstrated an association between various perinatal factors and placental inflammation. It is anticipated that the GII will provide a novel genomics tool for quantifying placental inflammation, allowing for further investigation of causes, and ultimately the prevention, of inflammation in the placenta. Highlights: The GII highlights inter-individual differences in placental inflammation. The GII displayed differential expression levels in association with self-reported race. Being married was associated with a lower GII than being single for Black women. Steroid use during delivery did not decrease fetal-side placental inflammation.